Search for Legionella pneumophila in domestic water system in Benin Metropolis - M.K. Ayanlere; I.N. Ibeh (Journal of Applied Sciences and Environmental Management, 2018)
Legionella species, a Gram negative bacterium is the causative agent of Legionnaires’ disease, a potentially fatal pneumonic syndrome of widely recognized public health importance. The aim of the study was to determine the presence of Legionella pneumophila in domestic water (borehole) in Benin metropolis by cultural method. One hundred and ninety-eight (198) water samples from the eight-two facilities (grouped into three: public apartments/hotels, private apartments and eateries) were cultured on BCYE made selective with the addition of legionella supplement IV and growth supplement after concentration and heat treatment at 500C for 30 minutes and incubated at 370C. Isolates were identified by doing gram stain, oxidase, catalase and hippurate test, final identification was done by using PCR, sequence and blast search using National Center for Biotechnology Information (NCBI). The results obtained showed that Legionella pneumophila or Legionella species was not isolated though other bacteria (such as Burkholderia bacterium MSMB7 (32%), Pseudomonas antarctica (28%), Cupriavidus gilaridii (14%), Microbacterium paraoxydans (14%), Bacillus thuringensis (4%), Bacillus cereus (2%), Acinetobacter johnsonii (6%)) were detected. In conclusion zero percent (0%) prevalence of Legionella species in the water systems investigated though other bacteria with pathogenic potential were recovered. This finding suggests that water systems in Benin metropolis may not present vehicles for the transmission of diseases associated with Legionella species.